Molecular and pathotypic characterization of new Xanthomonas oryzae strains from West Africa - (:unkn) unknown (My University, 2007)
DNA polymorphism analysis and pathogenicity assays were used to characterize strains of Xanthomonas oryzae pv. oryzae and Xanthomonas oryzae pv. oryzicola collected from rice leaves in West Africa. Restriction fragment length polymorphism (RFLP), repetitive sequence-based polymerase chain reaction, fluorescent amplified fragment-length polymorphism (FAFLP) analyses were assessed for molecular characterization, while pathogenicity was tested by leaf clipping and leaf infiltration. Dendrograms were generated for the data sets obtained from RFLP analysis and repetitive polymerase chain reaction suggesting that the interrelationships between strains were dependent on the technique used. In all cases, data showed that African strains of X. oryzae pv. oryzae form a group genetically distant from Asian strains. FAFLP analyses separated the X. oryzae strains into three groups with significant bootstrap values. A specific and intriguing feature of African strains of X. oryzae pv. oryzae is a reduction in the number of insertion sequence elements and transcription activator-like (avrBs3/pthA) effector genes, based on the molecular markers employed in the study. In addition, pathogenicity assays conducted with African strains of X. oryzae pv. oryzae on a series of nearly isogenic lines (NILs) identified three new races. Finally, leaf infiltration assays revealed the capacity of African strains of X. oryzae pv. oryzae to induce a nonhost hypersensitive response in Nicotiana benthamiana, in contrast with Asian X. oryzae pv. oryzae and X. oryzae pv. oryzicola strains. Our results reveal substantial differences between genomic characteristics of Asian and African strains of X. oryzae pv. oryzae
Keywords: African Research